Peningkatkan Hasil Belajar Al-Qur’an Hadis Melalui Metode Discovery Learning Siswa Kelas I Mi Bustanul Ulum 01 Mlokorejo - Siti Nur Kholisoh (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Class action research on students in class I MI Bustanul Ulum 01 mlokorejo motivated by initial observations that show low student learning outcomes, can be seen based on the average value of the results of pre-cycle students on the subject of knowing the letters hijaiyah and harakatnya is 66.67%. The average value is still below the minimum completeness criteria (KKM) set by the school, which is 70. This shows the low learning outcomes of students on the material to know the letters hijaiyah and harakatnya. The purpose of this study was to determine the implementation of the discovery larning learning method in improving student learning outcomes in each student cycle in class I MI Bustanul Ulum 01 Mlokorejo. The research method used is Class Action Research (PTK). The research was conducted in two cycles, each cycle consists of planning, implementation of action, observation, and reflection. The subject of this study was conducted on first grade students Mi Bustanul Ulum 01 Mlokorejo totaling 20 students. Data collection used in this study is qualitative and quantitative data. Qualitative Data in the form of observation sheet of discovery larning learning model implementation. While quantitative data in the form of data obtained from 1) the percentage of implementation of learning models obtained from the number of answers on the observation sheet, and 2) the percentage of completeness and incompleteness of student learning outcomes by using the discovery learning learning method. The results showed that the application of the discovery learning method can improve learning outcomes Al-Qur'an Hadith hijaiyah letter material first grade students MI Bustanul Ulum 01 mlokorejo academic year 2023/2024. Learning outcomes of the Qur'an Hadith hijaiyah letter material first grade students MI Bustanul Ulum 01 Mlokorejo academic year 2023/2024 increased from pre-cycle learning outcomes obtained an average of 66.75% with a percentage of completeness of 55%; cycle I obtained an average of 70.1% with a percentage of completeness of 65%; and Cycle II obtained average learning outcomes of 78.9% with a percentage of 90% completeness.